The KnotLink Game on Families of Whitehead and Pretzel Links - Adams, Hunter; Christensen, Megan; Friedel, Brooke; Henrich, Allison; Neel, David (The PUMP Journal of Undergraduate Research, 2025)
In this paper, we study the KnotLink Game, a two-player game that can be played on the shadow of a knot or link diagram. This game was introduced by Adams, Henrich, and Stoll, who investigated winning strategies on certain infinite families of rational links. We focus our work on determining winning strategies for two additional infinite families of links: the pretzel link family and a family of Whitehead links.